International Travel Patterns and Travel Risks of Patients Diagnosed With Cancer1. Issue 2 (30th January 2013) - Mikati, Tarek; Taur, Ying; Seo, Susan K.; Shah, Monika K.
Abstract : Background: Immunocompromised travelers living with cancer can be at increased risk of travel‐related illnesses. Their international travel patterns and associated risks remain largely unknown. Methods: This was a retrospective cohort study of all patients diagnosed with cancer who presented for pre‐travel health advice between January 1, 2003 and June 30, 2011. Demographics, travel patterns, and infectious diseases exposure risks of immunocompromised travelers were characterized and compared with those of immunocompetent travelers. Reported travel‐related illnesses were assessed in both groups. Results: A total of 149 travelers were included in this study. Fifty‐one percent had solid tumors, 32% had hematological malignancies, and 17% underwent stem cell transplantation. Seventy travelers (47%) were immunocompromised. Immunocompromised travelers had similar demographics, trip itineraries, and infectious diseases exposure risks to hepatitis A, malaria, typhoid fever, and yellow fever as immunocompetent travelers. Most of the reported travel‐related illnesses were of minor nature. Conclusion: Travelers with cancer who have impaired immunity had similar infectious diseases exposure risks and travel patterns as travelers whose cancer is cured or in remission. Improved understanding of travel patterns and risks of patients with cancer may assist in providing more focused pre‐travel health interventions to this complex subset of travelers.